Diseño de un sistema de costos en la empresa de productos lácteos Campo Fino, Salcedo - Lozada Pérez, Jessica Aracely (2022)
This integrative project was developed in the dairy products company "Campo Fino" dedicated to the processing of raw milk for the production and marketing of its derivatives; the problem of the entity is that it lacks a cost system that allows it to record information related to the disbursements made in the production process, therefore, it does not assign the costs in a fair and reasonable manner when obtaining the finished product. The objective of this work is to implement a cost system through the identification of cost elements, for the determination of the actual cost of production in the third quarter of the year 2021. The methodology used is a quantitative approach with a descriptive, field and analytical type of research; techniques such as direct observation and survey directed to the accountant and production manager were used to collect data related to production costs; the information obtained through the development of the research allowed choosing the process costing system considering the productive characteristics of the organization. The elaboration of dairy products consists of three fundamental processes such as: reception, preparation and packaging; when designing the cost system, the raw material, labor and general manufacturing costs were identified to determine the unit and total cost of its product line through the technical calculation of the respective reports of quantities and costs in order to obtain real and accurate information of the costs incurred for the construction of the set of financial statements that reflect the profitability of the company during the period to make an adequate decision making for the benefit of the entity. It is recommended to apply the proposed cost system in the next periods to identify the real utility of the finished products and obtain results that contribute to improve the accounting management through the correct control of resources and expenses, focusing on achieving the proposed objectives and administrative efficiency.